Prudential Principle Dalam Restrukturisasi Pembiayaan Di Perbankan Syari’ah Era Pandemi Covid 19 Perspektif Maslahah Mursalah - Prasetian Dewi, Arlinta (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2022)
This paper aims to dig deeper into the prudential principle that must be applied by Sharia banking in establishing a restructuring of financing in the perspective of Maslahah. That, in this era almost all debtors were impacted by Covid 19, so the challenge of restructuring implementation became much heavier, this requires banking to be much more observant in analyzing companies or debtors affected. There is a possibility of moral hazard by debtor that potentially resulted in Bank loss. On the other hand, a restructuring policy should be done at this pandemic to achieve mutual benefits, both debtors and creditors. The result of this research is, the prudential principle is absolutely necessary, so that the restructuring policy can run well and precisely on the target with guideline on the principles of maslahah. Sharia Banking also needs a new strategy in answering this pandemic Era restructuring challenge. Among them must have a new navigation map and debtor mapping clearly, business type selector to be restructured in accordance with the rules established by the government, digital banking product services, help customers connect with the online UMKM (Unit Usaha Mikro Kecil Menengah) community such as UMKM Go Online, verify the guarantee of credit financing in the field through video Call or zoom, business mentoring by RM (relationship manager). Then all the things that are done to apply the prudential principle is allowed in a maslahah.